Data Classification and Personal Care Management System by Machine Learning Approach - G. Pradeepini, Dr; Pradeepa, G; Tejanagasri, B; Harsha Gorrepati, Sri (International Journal of Engineering and Technology, 2018)
The ace system devices are expected as a key half inside the change of welfare as to such an extent as consistent discerning of patients treatment and preservation of E-pharmaceutical structure. The basic test that patients went up against is that the truth of problem in achieving specialist authorities. This paper proposes Associate in nursing keen structure which will give self-care what is a considerable measure of, checking system which will reproduce the patient in sight of his/her disorder. The methodology are at regardless of reason a patient sends his insight concerning his biopsy and entirely unexpected tests, the system can choose regardless of whether the condition is fundamental or not. In unimportant condition, the sharp system can give the recommendations of which psychological disorder he/she is facing. The structure used can revive information methodically with understanding and learning algorithms. A machine-learning estimation was directed to play out the gathering procedure.Â
Keywords: Psychological disorders; Machine Learning Algorithm; Naïve Bayes; PTSD; ASD; Health-care